PERAN POLA ASUH DEMOKRATIS ORANGTUA TERHADAP PENGEMBANGAN POTENSI DIRI DAN KREATIVITAS SISWA - Harbeng Masni (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Pattern foster parent is the overall interaction of parents with children, where parents stimulate their children by changing attitudes, behavior, attention, rules, discipline, reward and funismant, knowledge and response to the wishes of his son, as well as the values that are considered appropriate by the parents, so that children can be independent, grow and develop in a healthy and optimal. The role of democratic parenting applied parents make children become people who are willing to accept criticism and respect for others, have high self-confidence and is able to be responsible for their social life. Potential is the basic capabilities of a person who is still hidden and has the possibility to be developed if it is supported by the participation of the environment, exercise and adequate facilities, while there are four kinds of potential possessed by humans, namely, intellectual potential emotionally, spiritually and physically to be able to develop the potential of innovative ideas is needed, therefore i oneself and one's creativity can flourish if it is accompanied by various supporting factors such as family, school, environment and technology. Recognizing the potential of their children is one of the old rang effort in facilitating the development of children There are three models of counseling approaches that can be studied as a support and knowledge for the natural parents guide their children including counseling directive, non-directive counseling and eclectic approach. Keywords: the role of parents, democratic parenting, potential pattern creativity